FAKTOR MOTIVASI WISATAWAN NUSANTARA MILENIAL MENGINAP DI BOBOCABIN KINTAMANI - Riadi Sugita Putra, I Komang; Indrawati, Yayu; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024)DO - 10.24843/IPTA.2024.v12.i02.p11, 2025)
Bobocabin Kintamani is one of 103 active accommodations in Kintamani (2021), and was named number 2 of 11 campsites in Kintamani by Tripadvisor (2024). Based on visit data in January 2023-March 2024, 1,177 tourists stayed at Bobocabin Kintamani, and this was dominated by millennial domestic tourists. This research aims to determine the factors that motivate millennial domestic tourists to stay at Bobocabin Kintamani. The sample for this research was 100 millennial domestic tourists who had stayed at Bobocabin Kintamani. Data collection techniques were carried out using observation, questionnaires, interviews, literature study, and documentation. Data analysis techniques using factor analysis using the SPSS for Windows Version 29.0.2.0 program. The characteristics of the respondents were dominated by tourists from DKI Jakarta, female, aged 24-28 years, unmarried, Bachelor's degree (S1), profession as a private employee, expenditure range of IDR 1,000,000-2,000,000 (40%) and IDR 2,001. 000-3,000,000 (40%), visit only once with a visit duration of 1-2 days, and use a car. The results of factor analysis show that there are eight factors that encourage millennial domestic tourists, namely (1) Self Fulfillment and Social Interaction, (2) Family Bonds, (3) Wish Fulfillment, (4) Prestige, (5) Romance Moment, (6) Escape from Routine and Having Fun, (7) Relationship, (8) Novelty Seeking. As well as three factors that attract millennial domestic tourists, namely (1) Services, Facilities and Location, (2) Static Factor, (3) Information. The most dominant factor driving the motivation of millennial domestic tourists to stay at Bobocabin Kintamani is the "Self Fulfillment and Social Interaction" factor. Meanwhile, the dominant factor that attracts the motivation of millennial domestic tourists to stay at Bobocabin Kintamani is the "Services, Facilities and Location" factor.